The i-Motif as a Molecular Target: More Than a Complementary DNA Secondary Structure - Susie L. Brown; Samantha Kendrick (MDPI AG, 2021)
Stretches of cytosine-rich DNA are capable of adopting a dynamic secondary structure, the i-motif. When within promoter regions, the i-motif has the potential to act as a molecular switch for controlling gene expression. However, i-motif structures in genomic areas of repetitive nucleotide sequences may play a role in facilitating or hindering expansion of these DNA elements. Despite research on the i-motif trailing behind the complementary G-quadruplex structure, recent discoveries including the identification of a specific i-motif antibody are pushing this field forward. This perspective reviews initial and current work characterizing the i-motif and providing insight into the biological function of this DNA structure, with a focus on how the i-motif can serve as a molecular target for developing new therapeutic approaches to modulate gene expression and extension of repetitive DNA.